أوجه رحمة الزوج بزوجته وانعكاساتها على نفسية الزوجة ومستوى تقديرها لذاتها - زقاوة, أحمد; ياسين, أمينة (جامعة الوادي University of Eloued, 2018)
تتناول الدراسة الحالية الإجابة عن الإشكالية التالية: ما أوجه رحمة الزوج بزوجته؟ وما انعكاساتها على نفسية الزوجة وعلى مستوى تقديرها لذاتها؟ وهل توجد فروق في أوجه رحمة الزوج بزوجته تعزى لبعض المتغيرات الدخيلة؟ استخدم الباحثان المنهج الوصفي التحليلي، من خلال تصميم ثلاث أدوات بحث تم تطبيقها على 188 زوجة متعددة المميزات. وبعد التحليل الإحصائي للمعطيات، خلصت النتائج إلى: أن أوجه رحمة الزوج بزوجته هي معنوية بالدرجة الأولى. وكلما انخفضت مدة الزواج زادت أوجه الرحمة المعبر عنها من قبل الأزواج. وتسجيل مستوى مرتفع في كل من مقياس الآثار النفسية ومقياس تقدير الذات لدى الزوجات جراء المعاملة الرحيمة لأزواجهن. ثم تم تقديم جملة من التوصيات.ABSTRACT:The current study answers the following questions: What is the mercy of the husband with his wife? What are the implications for the wife's psychology and self-esteem? Are there differences in the mercy of the husband with his wife attributed to some exotic variables? The researchers used the analytical descriptive approach by designing three search tools applied on(188) multi-featured wives. After the statistical analysis of the data, the results concluded that: The mercy of the husband with his wife is primarily moral. The lower the length of the marriage, the greater the compassion expressed by the husbands. And recording a high level in both the psychological impact measure and the self-esteem measure of wives due to the compassionate treatment of their husbands. Some recommendations were given.
مقال
Keywords: أوجه الرحمة؛ الأثار النفسية؛ تقدير الذات لدى الزوجة; the mercy; wife psychology; self-esteem